If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + 13 = 0 Reorder the terms: 13 + 8y = 0 Solving 13 + 8y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 8y = 0 + -13 Combine like terms: 13 + -13 = 0 0 + 8y = 0 + -13 8y = 0 + -13 Combine like terms: 0 + -13 = -13 8y = -13 Divide each side by '8'. y = -1.625 Simplifying y = -1.625
| 8(y-3)-3=56 | | 28y+5=49 | | 28y+5=27 | | 2x+167=11x-13 | | 7m-11=59 | | 9h+6=87 | | 7m+3=59 | | sin(2x+5)=sin(x-1) | | x^3-6x^2+20x=0 | | 2x^3-6x^2+20x=0 | | x+2.5z=18 | | 27x+11y+6z=1200 | | ln(x+7)=2 | | (60-d)(40-2d)=0 | | (60-d)(40-2d)=1312.5 | | 2a+4b+8c=200 | | x^3-2x^2-7x+6=0 | | 24(x+4)=24 | | 46(x-2)=18 | | 83(n+4)=7 | | 108(n-3)=12 | | (10+15)x(2+3)= | | 85n-6=19 | | 104y-3=14 | | (10)8-x+x=3[(10)x+8-x]-16 | | 2(-y+1)=5y+2(6-y) | | 3(x+2.98)=2x | | 123x+1=21 | | 13x+9y=136 | | 13+9y=136 | | 13x=9y+136 | | 164x+17=9 |